2016
DOI: 10.1515/hukin-2015-0160
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ Preferences for Continuing Coaching Education in South Africa

Abstract: The purpose of this study was to examine coaches’ preferences for continuing coaching education. The sample consisted of 122 male and 102 female coaches from the Gauteng Province of South Africa who were purposively recruited to participate in this study. The results of this study showed that the coaches wanted to learn more about motivational techniques, advanced instructional drills, advanced first aid, goal setting, character building and conditioning drills. The results further indicated that sport coaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 8 publications
3
12
0
2
Order By: Relevance
“…Research has shown that over recent years, youth sports has grown comprehensively, and so too has the need for qualified coaches. This has resulted in the development of the International Sport Coaching Framework (ISCF) (6). The ISCF provides a standard for evaluating and developing coaching qualifications, encourages education and training, and outlines ethical guidelines and practice standards, which in turn could lead to a decrease in the amount of injuries (6,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that over recent years, youth sports has grown comprehensively, and so too has the need for qualified coaches. This has resulted in the development of the International Sport Coaching Framework (ISCF) (6). The ISCF provides a standard for evaluating and developing coaching qualifications, encourages education and training, and outlines ethical guidelines and practice standards, which in turn could lead to a decrease in the amount of injuries (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…There are different ways to prevent sport injuries, which include factors such as technique, previous injuries, and parental pressure, or winning a game (6). Research primarily focuses on the potential causes of injuries in youth sports, often stressing the unique physiologic and biomechanical aspects of the growing body, while research into the effect of life stress is growing (2,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The question required for the process of training professional skills, recommended attention of researchers in the field of sports training [1][2][3][4] In addition , some previous research has been criticized as limited to the studied performance of trainers because of their loss of the formative or educational factor, which can explain the behavior of the teacher between; Accordingly, about his interest in research to study the ideas of trainers and knowledge, and what it referred to him [5]. Although professionalism reflects the ability of trainers to apply their knowledge and beliefs, they are looking for more effective practice.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the value of both sport and PE, expressed by both the educators and learners, challenges remain with regard to the implementation sports, which means because there was no internalization, implicit therein, thus no satisfaction of the need for relatedness. In relation to the preceding, findings of research conducted on the effect of PESS needs support educator training [112][113][114] suggest that participants' perceptions of PESS and motivational levels to teach and coach a sport or to participate have indeed improved after the needs-support educator training.…”
Section: Discussionmentioning
confidence: 99%